2015
DOI: 10.1016/j.jnucmat.2014.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Fe/Y2O3 interfaces as a model system for oxide-dispersion-strengthened ferritic alloys

Abstract: The fundamental mechanisms underlying the superior radiation tolerance properties of oxidedispersion-strengthened ferritic steels and nanostructured ferritic alloys are poorly understood. Thin film heterostructures of Fe/Y 2 O 3 can serve as a model system for fundamental studies of radiation damage. Epitaxial thin films of Y 2 O 3 were deposited by pulsed laser deposition on 8% Y:ZrO 2 (YSZ) substrates with (100), (110), and (111) orientation. Metallic Fe was subsequently deposited by molecular beam epitaxy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Physico-chemical methods can be tentatively classified into ion implantation [72][73][74] , epitaxy including chemical vapor deposition (CVD) and physical vapor deposition (PVD) as well as related variants such as electron beam PVD, [75] molecular beam epitaxy, [76] magnetron sputtering [77] and pulsed laser deposition (PLD). These methods are typically capable of producing samples of lateral dimensions of 10 mm (or less if required) and layers ranging from 10 nm to 1 µm thickness that generally serve as model systems for the investigation of the behavior of interfaces between Fe-matrix and oxide-particles, e.g.…”
Section: E Physico-chemical Methodsmentioning
confidence: 99%
“…Physico-chemical methods can be tentatively classified into ion implantation [72][73][74] , epitaxy including chemical vapor deposition (CVD) and physical vapor deposition (PVD) as well as related variants such as electron beam PVD, [75] molecular beam epitaxy, [76] magnetron sputtering [77] and pulsed laser deposition (PLD). These methods are typically capable of producing samples of lateral dimensions of 10 mm (or less if required) and layers ranging from 10 nm to 1 µm thickness that generally serve as model systems for the investigation of the behavior of interfaces between Fe-matrix and oxide-particles, e.g.…”
Section: E Physico-chemical Methodsmentioning
confidence: 99%
“…An epitaxial Fe/Y 2 O 3 interfaces were proposed as a model system for oxide-dispersion-strengthened ferritic alloys study. [25] It has been found that Fe is partially epitaxial on Y 2 O 3 /YSZ(110), polycrystalline on (100) and (111). Well-ordered crystallites of Fe with both epitaxial and non-epitaxial orientations on Y 2 O 3 are a promising model system for fundamental studies of radiation damage phenomena.…”
Section: Dispersion Of Nanoparticles In Steelsmentioning
confidence: 99%
“…[23,24] The combination of the instinct radiation resistance with other functional materials like graphene, oxides, and so on, may build plenty of phase boundaries as sinks for lowering defects as well as introduce supernumerary properties like thermal stability or reinforce strength to the matrix materials. [25][26][27] On basis of the research works reported during the past few years, this paper presents the recent progress on interfaces including the grain boundaries and hetero-phase interfaces in nanomaterials for nuclear radiation tolerance. The related research on nanomaterial interfaces including the radiation damages within nanomaterials, the grain boundary construction in nanocrystalline materials, as well as the interfacial engineering of hetero-phase interfaces in nanocomposites for nuclear radiation tolerance are reviewed and summarized.…”
Section: Introductionmentioning
confidence: 99%
“…However, irradiation and compositional stability studies at these oxide/matrix interfaces are challenging due to the small size of the oxide phase particles [14], their complex chemistry, and the differing affinities of oxygen to the various metallic constituents of the alloy, which might play an important factor in the changes in the microstructure and microchemistry at the metal/oxide interface [23]. Therefore, in order to reduce the complexity of the analysis, ideal 2-D emulations, with a simplified chemistry, can be performed by synthetizing thin film bilayer or multilayer composite and used as model systems for studies concerning radiation response of solid interfaces [24,25].…”
Section: Introductionmentioning
confidence: 99%